Barriers to completion of secondary education among Khmer student - Lieu Thanh Tam (Southern Leyte State University, 2020)
Education is one pivotal factor that determines an individual’s ability to move up the ladder of success. A strong educational environment is essential for any learner to attain successful mobility in his or her later life as an adult which bears societal impact. Completing secondary education is essential for any chance to achieve educational and financial success in life but failure to do so can pose threat to the country’s economy. In spite of the numerous evidence that completion to secondary education paves the way to better life-personally, professionally, or financially in adulthood, waves of high school students drop-out every year which is the case of the Khmer secondary school students. This study examines the factors that cause Khmer students drop out. Significant outcomes of the research showed ecological related barriers: family, school, student self-efficacy, and cultural. It is with hope that by examining the barriers to completing secondary education among Khmer high school students, the findings will contribute in reducing the dropout rate of Khmer students in Tra Vinh province which can serve as one of the inputs for a comprehensive approach to address the situation.